Reference urinary biopyrrin level and physiological variation in healthy young adults: relation of stress by learning. Issue 1 (January 2020) - Tada, Satoshi; Shiota, Atsuko; Hayashi, Hidehiro; Nakamura, Takehiro
Abstract: Background: Biopyrrins are end products of oxidation reactions of bilirubin with reactive oxygen, and urinary biopyrrin (UBP) levels might increase under oxidative stress. The authors examined the reference UBP level for healthy adults and its physiological variation in 40 healthy volunteers recruited from among students of our university (20 students each from third-year and fourth-year), and compared the results with data on 8-hydroxy-2-deoxyguanosine (8OHdG). Methods: UBP and 8OHdG levels could be considered as oxidative stress markers. The UBP levels were measured with a competitive ELISA kit using biopyrrin antibody 24G7, according to the manufacturer's protocol. 8OHdG levels were measured with a Highly Sensitive 8-OHdG Check kit. UBP and 8OHdG measurements were performed in triplicate and means values calculated. For both parameters, creatinine (Cr) correction was performed using urinary creatinine levels measured by an enzymatic method. Results: A comparison of the UBP levels between different grades revealed that the third-year students under high stress from clinical training and other course work tended to have a higher UBP level than fourth-year students. Therefore, we compared the current UBP levels in fourth-year students (samples collected in 2018) with their UBP level when they were in the third-year (samples collected in 2017) to examine the annual change. We found that the UBP level in 2017 samples was significantly higher than that in 2018 samples (P < 0.05). No difference in the 8OHdG level. Additionally, no effect of menstrual stress on the UBP level was observed. Conclusions: These results suggest that the UBP levels may be related to school-related stress and menstruation has no effects on urinalysis results. Abstract : Health Professions; Biological Sciences; Analytical chemistry; Oxidative Stress; Quality of Life; Occupational Health; Educational Psychology; Health Education; urinary biopyrrins, 8OHdG, oxidative stress, reference value, school-related stress